Relations between fractional models with three-parameter Mittag-Leffler kernels - Fernandez, Arran; Abdeljawad, Thabet; Baleanu, Dumitru (Springer, 2020)
We consider two models of fractional calculus which are defined using three-parameter Mittag-Leffler functions: the Prabhakar definition and a recently defined extension of the Atangana-Baleanu definition. By examining the relationships between the two, we are able to find some new properties of both, as well as of the original Atangana-Baleanu model and its iterated form.
Keywords: Fractional calculus; Mittag-Leffler functions; Atangana-Baleanu fractional calculus; Prabhakar fractional calculus